Simulation and design of a standing table for patients with low-level spi-nal cord injury or cauda equina injury (Revista de Investigaciones Universidad del Quindío, 2012)
This project shows all the methodology used to design equipment for the physical therapy of patients suffe-ring from low-level spinal cord injury, cauda equine injury or herniated disc, which seeks to provide a more efficient physiotherapy that currently offered, in this document contains all the equipment design process fo-llowing the standards established for the manufacture of these electro mechanical equipment.
Keywords: Table of standing; spine; herniated disc; cauda equine injury; Cyriax Physiotherapy Centre